Nonce Words in Mass Media Discourse (A Case Study of Travel Journalism Innovations) - Nykytchenko, Kateryna (Communication Today, 2025)
The English language nowadays is significantly changing, responding to the opportunities of a rapidly evolving world. The lexical level is intrinsically most liable to changes, albeit the constantly increasing number of new words inevitably entails some obscureness and preposterousness. This pilot study is intended to shed light on the dubious nature of ‘nonce words’ which, on the one hand, help express speaker’s thoughts and convey implicit preferences and, on the other hand, serve as a barrier to understanding the message. The article covers the notion of nonce words, their place and role in mass media discourse. The author determines the key features and functions of nonce words in media discourse in general and travel journalism in particular. The choice of the data is predetermined by the popularisation of travel media as a trend for ‘infotainment’ in modern mass media. The text elaborates cognitive features of word-formation, which makes possible to investigate the interaction of mind, language and reality in the act of designation and reveal cognitive mechanisms that underlie the designation of different fragments of the surrounding world. Resting on comprehensive methods applied to the study, the researcher affirms that cognitive mechanisms, operations and procedures underlie aggregated, condensed and modified types of occasional word-formation. Particular attention is paid to portmanteau words as the most productive way of creating nonce words in mass media discourse.